Impactos sociambientais da Hidrelétrica Santo Antônio do Jari: a percepção de comunidades afetadas - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The research analyze the socioeconomic and environmental impacts produced by the construction of the Santo Antônio do Jari Hydroelectric Power Plant, based on the perception of the affected communities. The research was carried out with the communities in the city of Laranjal do Jari, in Amapá, residents of the area of direct influence of the hydroelectric plant. This study is a qualitative research, in which field research was carried out between the months of July and November of 2018. Data were collected through snowball sampling and the application of 42 semi-structured forms with open and closed questions that allowed the identification of local stakeholders' expectations regarding the hydroelectric plant and the socioeconomic and environmental impacts resulting from the presence of the hydroelectric plant in the region and questions related to access to natural resources after the installation of the hydroelectric plant. To assist the analysis, secondary data sources were explored such as studies and reports of environmental impact and monitoring of hydroelectric activities. For the analysis and interpretation of the data, the Bardin content analysis technique was used. The results show that the communities affected by the Santo Antônio do Jari hydroelectric plant experience the negative impacts resulting from the environmental changes generated, mainly by the formation of the reservoir. These impacts include reallocating communities, reducing availability and access to natural resources, loss of livelihoods, threats to food security, and lifestyle change. The reality of the communities is marked by relocation, by the decline of the availability of natural resources, impairing food self-sufficiency, the use of areas with cultural and spiritual values, and interfering with socioeconomic activities. For the communities, they have to adapt to the new imposed life and to establish new socio-cultural relations with the new physically transformed environment
Keywords: Usina Hidrelétrica de Santo Antônio do Jari (AP); Laranjal do Jari (AP); Comunidade; Territorialidade humana - Aspectos sociais - Amapá; CNPQ::CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA DA POPULACAO; GESTÃO, TECNOLOGIA E INOVAÇÃO AMBIENTAL; CIÊNCIAS AMBIENTAIS DA AMAZÔNIA